Regional and inter-regional input-output model as a planning tool for economic development in Malaysia - Hassan, Mohd Khairul Hisyam (2015)
This study examines the importance of regional development planning to economic growth through the construction of regional and inter-regional input-output tables for East and West Malaysia. It is particularly important because only limited past studies have been conducted on the construction of regional and inter-regional input-output tables at the regional or state level in Malaysia and also, the usage of input-output model has received much attention in many countries as a planning tool for economic development. With East and West Malaysia as case studies, the LQ and RAS techniques were employed to construct regional input-output tables for both regions for the year 2005. These tables were used to construct the inter-regional input-output tables for the regions applying the model of Miller and Blair (2009). The spillovers and feedback analyses describe the interdependency on trade either inter-regional or foreign, while those of linkages and multipliers help to determine the key or potential sectors in each region which affect economic growth. The spillovers and feedback, linkages and multipliers were calculated. Several important conclusions can be drawn from the study. The 2005 output of East and West Malaysia was contributed mainly by the mining and quarrying, and electronics and non-electronic sectors respectively. In addition, the calculated spillover and feedback coefficients show the reason why the dependency on foreign trade recorded the higher value compared with each other’s trade for both regions. The main reason for this scenario is because most of the raw materials for production and final consumption were satisfied by foreign trade and this also created very huge leakages for both regions. Lastly, based on the linkages and multipliers analysis in this study, we found that the agriculture and livestock; forestry and logging; food manufacturing; petroleum products; and motor vehicles and other transport; sectors were among the sectors with the highest backward linkage and multiplier coefficients in the East and West Malaysia regions. So, putting additional investment into these sectors will generate more output to the overall economic performance of these regions because of the ability of these sectors to attract the other sectors in the economy.